Violencia, Educación y Teoría Mimética. Hacia una mímesis positiva - Cantero, María Araceli Oñate (2021)
Understanding the complexity of bullying and school violence is a necessary prior step to the proposal of any prevention model whose effectiveness is postulated and whose foundation is the centrality of the person and the search for the truth in the educational environment, a privileged meeting place. The Mimetic Theory described by Girard not only explains the roots of the violence present in the classroom but also constitutes its anthropological foundation and the appropriate theoretical framework to reverse it, in addition to recognizing in the innocent victim the cornerstone of the education building.International requirements, reforms of the Penal Code and child protection mechanisms remind public and private institutions of their responsibility to guarantee a safe environment for each and every one of their schoolchildren. The Commitment of the entire educational community, students adopting Good Treatment Protocols, early identification through periodic evaluation of violence, management of attitudes in the classroom and psychosocial evolution mentoring; triple institutional, psychosocial and personal approach of the AVE Program for the Prevention of Violence and Bullying which, based on the contributions of René Girard and Jean Christian Fauvet, has demonstrated its effectiveness in the eradication of bullying, discrimination and violence from our classrooms.